Ionic liquid and deep eutectic solvent-enabled food freshness sensing: From molecular interactions to integrated intelligent monitoring systems - Xinhui Zhou; Yuan Huang; Yuping Liu; Zhangyan Sun; Yuxiao Hu; Mingfeng Xu; Xueqin Yang; Rongrong Yu (Trends in Food Science & Technology, 2026)

Characterization of Pichia pastoris protease and its application in improving the quality and storage stability of dried pork jerky - Ziyuan Zhang; Yuan Huang; Mengning Zhao; Yixin Zhang; Mingfeng Xu; Fangda Sun; Rongrong Yu (Food Chemistry, 2026)

Interference effects of aerodynamic forces for high-rise buildings with different side ratios - Haiwei Xu; Chengxi Pan; Mingfeng Huang; Wenjuan Lou; Zuopeng Wen; Ahsan Kareem (Engineering Structures, 2026)

Conjunctive analysis of BSA-Seq and KASP markers unveils the preliminary candidate genes controlling chalkiness of rice grain - Mingfeng Tang; Zhongwei Wang; Tingting Zeng; Tingting Fu; Wei Zhang; Yongchuan Huang; Yanjie Yao; Yongyang Fan; Xianwei Zhang (Euphytica, 2026)

Time-frequency simulation model of downburst wind and its effects on wind turbine responses - Qiushuang Lin; Yansong Wang; Mingfeng Huang; Kang Cai (Engineering Structures, 2026)

Probabilistic inference of wave parameters and extreme wind-wave analysis for OWTs under typhoon conditions - Shidong Liang; Mingfeng Huang; Guoqing Jia; Kang Cai; Qing Wang; Yanbo Wang (Ocean Engineering, 2026)

GNSS/MEMS INS tightly coupled algorithm for agricultural machinery navigation enhanced by random forest-based behavioral state awareness - Yihang Feng; Guanwen Huang; Mingfeng Wang; Xin Li; Zhenhong Li; Hang Li; Kai Zhang; Ce Jing (Computers and Electronics in Agriculture, 2026)

CYP321A9 mediates the metabolism of two diamide insecticides, chlorantraniliprole and tetrachlorantraniliprole in Spodoptera frugiperda - Wenjing Cao; Mingfeng Huang; Yongheng Zhang; Meng Long; Xuesheng Li (Pesticide Biochemistry and Physiology, 2026)

An automated and intelligent monitoring system for shield tunneling muck evaluation integrating multimodal data - Zeyu Yue; Linchong Huang; Yuexiang Lin; Yu Liang; Mingfeng Lei; Jianjun Ma (Journal of Cleaner Production, 2026)

A DFN–DEM approach to determine equivalent mechanical parameters of rock mass with different joint densities - Liang Wang; Shijie Zhou; Juan Huang; Mingfeng Lei; Yonggang Han; Jian Zhang; Chaojun Jia (Bulletin of Engineering Geology and the Environment, 2026)

CDC6 promotes the development and progression of clear cell renal cell carcinoma via upregulating RRM2 - Tianpeng Xie; Zanxuan Deng; Youping Ding; Peng Peng; Pan Rao; Yanqun Huang; Lizhen Li; Gaode Zou; Xiaofeng Zou; Mingfeng Xiang (Human Cell, 2025)

Redox state of NAD modulates the activation of Na-bicarbonate cotransporter NBCe1-B via IRBIT and L-IRBIT - Tianxiang Gui; Ying Liu; Mingfeng Fu; Han Wu; Pan Su; Xuhui Feng; Mengmeng Zheng; Zixuan Huang; Xudong Luo; Walter F. Boron; Li-Ming Chen (Science China Life Sciences, 2025)

Topology and element sizing optimization for performance-based design of wind sensitive tall buildings - Mingfeng Huang; Chunhe Wang; Wei Lin; Zhibin Xiao (Engineering Structures, 2025)

Motion adaptive vision-based vibration measurement and modal identification for the roof masts of a tall building - Mingfeng Huang; Xianzhe Li; Kang Cai; Ahsan Kareem (Engineering Structures, 2025)

A leader-adaptive particle swarm optimization with dimensionality reduction strategy for feature selection - Shanshan Yang; Bo Wei; Li Deng; Xiao Jin; Mingfeng Jiang; Yanrong Huang; Feng Wang (Swarm and Evolutionary Computation, 2024)

Multi-classification prediction of PM2.5 concentration based on improved adaptive boosting rotation forest - Tan Deng; Yingzi Jia; Ni Liu; Xiaoyong Tang; Mingfeng Huang; Wenzheng Liu; Xinjiang Hu; Yanling Gu (Journal of Environmental Chemical Engineering, 2024)

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

Dynamic response of a transmission conductor following delayed ice shedding by reduced-scale model test - Yuelong Zhang; Yong Guo; Wenjuan Lou; Weizheng Zhou; Mingfeng Huang (Cold Regions Science and Technology, 2024)

Formula model established through field application of glass slides and rapid analysis of pesticide residues in vegetables by ion mobility spectrometry - Yong Mei; Mingfeng Huang; Wayne Jiang; Gaoqing Yuan; Xuesheng Li (Food Control, 2024)

Comparison of batch, fed-batch and continuous operation modes for scalable polyhydroxyalkanoate (PHA) production and carbon sequestration from phenol - Qiuyue Tao; Heyun Huang; Mingfeng Yang; Yuqi Zou; Marie K. Harder; Qun Yan; Bo Liang; Ioanna Ntaikou; Georgia Antonopoulou; Gerasimos Lyberatos; Yi Zhang (Journal of Water Process Engineering, 2024)

Investigation of the Constitutive Damage Model of Rock Under the Coupled Effect of Freeze–Thaw Cycles and Loading - Yanni Zheng; Chaojun Jia; Mingfeng Lei; Juan Huang; Chenghua Shi (Rock Mechanics and Rock Engineering, 2024)

Comparative analysis of the effect of nano‑copper and Cu2O treatment on Cryptocaryon irritans tomonts in large yellow croaker (Larimichthys crocea) farming - Ying Zhou; Quanyin Liu; Kun Hu; Mingfeng Ge; Shengwei Xu; Chengyi Huang; Shan Jin; Rongrong Ma; Jianping Wang (Aquaculture, 2023)

S-dinotefuran affects the social behavior of honeybees (Apis mellifera)and increases their risk in the colony - Fu Zhang; Wenjing Cao; Yongheng Zhang; Jie Luo; Jiangan Hou; Lichao Chen; Guoqiang Yi; Honghong Li; Mingfeng Huang; Linxi Dong; Xuesheng Li (Pesticide Biochemistry and Physiology, 2023)

Insight into the effect of microplastics on the adsorption and degradation behavior of thiamethoxam in agricultural soils - Mingfeng Hu; Lulu Huang; Ya Wang; Huihua Tan; Xiangyang Yu (Chemosphere, 2023)

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

Seasonal pollution and surface characteristics of microplastics in surface water in the Wanzhou section of the Three Gorges Reservoir, China - Ying He; Qian Huang; Qilong Wang; Mingfeng Tang; Xiaoyu Lu; Fei Cheng; Guosheng Xiao (Environmental Science and Pollution Research, 2023)
The pollution of freshwater environments with microplastics (MPs) has attracted increasing attention owing to their threats to aquatic ecosystems and human health. Here, we sampled and analyzed MPs from mainstream, tributary, and backwater areas in the Wanzhou section of the Three Gorges Reservoir (TGR) in impoundment and flood periods. Microplastic pollution was the most severe in the backwater areas. The average abundance of MPs reached the highest value in the flood period (5.27±3.47×10 7 items km −2 ), which was 3–5 times that in the impoundment period. In the 0.3–5 mm size class, the 1–5 mm fraction was the most abundant, accounting for more than 81% in the flood period and 68% of the total MP particle abundance in the impoundment period in the mainstream and backwater areas. However, 0.3–1 mm MPs contributed more than 50% in the tributaries during the impoundment period. Polystyrene, polypropylene, and polyethylene MPs were detected in foam, fragment, sheet, and line-shaped MP particles. White, opaque, foamed polystyrene MPs contributed 32–81% to total MP particle abundance in the watershed. Microplastic particle surfaces showed signs of damage and oxidation, and ten different elements were found. Oxygen was clustered on the surface of foam and fragment MPs. Microplastic pollution was severe in the Wanzhou watershed. Especially in the backwater areas, oxidized MPs of variable shapes derived mainly from surface runoff in the flood period and sewage discharge in the impoundment period were abundant. The results of this study contribute to understanding seasonal pollution patterns and surface characteristics of MPs in the TGR and similar watersheds.

Machine Learning-Based Prediction of Dynamic Responses of a Tower Crane under Strong Coastal Winds - Qiang Li; Weijie Fan; Mingfeng Huang; Heng Jin; Jun Zhang; Jiaxing Ma (Journal of Marine Science and Engineering, 2023)
With the rapid development of the construction industry, tower cranes are increasingly used in coastal engineering. However, due to the complexity of their operating environment, tower cranes are vulnerable to typhoons, thunderstorms, and other extreme natural disasters. Therefore, it is becoming increasingly important to carry out safety warnings for the tower crane structure under the action of strong winds. In this paper, a real-time monitoring system for tower responses based on the Internet of things (IoT), which realizes long-term monitoring of the whole process of tower crane operation, was built. Based on the long-term monitoring data and the machine learning algorithm, two tower response prediction models were established. During the transit of super typhoon In-fa, the maximum displacement of the tower structure was predicted in advance, based on the measured wind speed data at the site, which is in good agreement with the displacement data monitored by the IoT. The results show that under strong winds, the non-working tower has a response lag, resulting in the fact that its maximum displacement does not correspond to the maximum wind speed moment at the site. This is mainly due to the weathercock effect of the tower in the non-working condition. The prediction model proposed in this paper can provide timely and effective safety warnings for the tower structure. It also can provide useful engineering references and scientific structural safety warning suggestions for the same type of tower cranes that do not have IoT monitoring systems installed.

Nitrogen Application Promotes Drought-Stressed Sugar Beet Growth by Improving Photosynthesis, Osmoregulation, and Antioxidant Defense - Hongliang Zhou; Pengjie Xu; Lijuan Zhang; Ruimin Huang; Mingfeng Yang; Kaiyong Wang; Hua Fan (Journal of Soil Science and Plant Nutrition, 2023)

Overexpressing 4-coumaroyl-CoA ligase and stilbene synthase fusion genes in red raspberry plants leads to resveratrol accumulation and improved resistance against Botrytis cinerea - Junxin Zhang; Xihuan Yan; Tiran Huang; Huan Liu; Fang Liu; Meixia Yang; MingFeng Yang; Lanqing Ma (Journal of Plant Biochemistry and Biotechnology, 2023)

Precursors and formation pathways of furfural in sugarcane juice during thermal treatment - Huimei Huang; Jiebo Chen; Mingfeng Zheng; Lulu Zhang; Hongfei Ji; Huajin Cao; Fengxia Dai; Lu Wang (Food Chemistry, 2023)

Effects of Microplastics on the Mineral Elements Absorption and Accumulation in Hydroponic Rice Seedlings (Oryza sativa L.) - Mingfeng Tang; Yongchuang Huang; Wei Zhang; Tingting Fu; Tingting Zeng; Yongdong Huang; Xiaoxia Yang (Bulletin of Environmental Contamination and Toxicology, 2022)

Anisotropic properties of shale and its impact on underground structures: an experimental and numerical simulation - Chaojun Jia; Qiang Zhang; Mingfeng Lei; Yanni Zheng; Juan Huang; Lichuan Wang (Bulletin of Engineering Geology and the Environment, 2021)

Antisense oligonucleotide technology can be used to investigate a circular but not linear RNA-mediated function for its encoded gene locus - Zhenxing Song; Ruirui Jia; Mingfeng Tang; Fei Xia; Haiyang Xu; Zhengguo Li; Chuan Huang (Science China Life Sciences, 2021)

Assessing SARS-CoV-2 RNA levels and lymphocyte/T cell counts in COVID-19 patients revealed initial immune status as a major determinant of disease severity - Mingfeng Han; Mengyuan Xu; Yafei Zhang; Zhongping Liu; Shasha Li; Tengfei He; Jinsong Li; Yong Gao; Wanjun Liu; Tuantuan Li; Zixiang Chen; Xin Huang; et al. (Medical Microbiology and Immunology, 2020)

Research on the construction risk control technology of shield tunnel underneath an operational railway in sand pebble formation: a case study - Mingfeng Lei; Dayong Lin; Qiyou Huang; Chenghua Shi; Linchong Huang (European Journal of Environmental and Civil Engineering, 2020)

Construction of a series of episomal plasmids and their application in the development of an efficient CRISPR/Cas9 system in Pichia pastoris - Yang Gu; Jucan Gao; Mingfeng Cao; Chang Dong; Jiazhang Lian; Lei Huang; Jin Cai; Zhinan Xu (World Journal of Microbiology and Biotechnology, 2019)

Monitoring canopy recovery in a subtropical forest following a huge ice storm using hemispherical photography - Runxia Huang; Xiaorong Jia; Yuduan Ou; Mingfeng Xu; Peiyun Xie; Zhiyao Su (Environmental Monitoring and Assessment, 2019)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)